VARIASI PAKAN DALAM MENDUKUNG PRODUKTIVITAS SAPI ACEH DAN SAPI BALI DI INDONESIA - Umaira, Syifa Thifal; Sahira, Rasyadhifa As; Firdus, Firdus; Allaily, Allaily; Sari, Widya (Prodi Ilmu Peternakan Universitas Muhammadiyah Cirebon, 2024)
The survival of Acehnese and Balinese cattle is affected by feed that contains nutrients to support the growth and productivity of livestock. Feed quality, quantity and continuity are problems that affect the productivity of local cattle in Indonesia. The most commonly used forages in feeding Aceh and Bali cattle are elephant grass dan field grass, while the most commonly used concentrates are palm fronds and corn. A combination of 80% forage and 20% concentrate tends to be better for increasing daily weight gain of Aceh and Bali cattle.